Breeding French Bean (Phaseolus vulgaris L.) for Resistance to Rust (Uromyces phaseoli Reben Wint.) - T S Aghora (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2007)
French bean is an important legume vegetable grown for its tender, green pods for both fresh consumption and processing. Rust, caused by Uromyces phaseoli, limits successful cultivation of this crop. Popular varieties like Contender, Pant Anupama, Pusa Parvathi, Arka Komal, Arka Suvidha, etc., are susceptible to this disease. The french bean variety, Arka Bold, having resistance to rust was used in hybridization with Arka Komal, a popular bush variety with high yield and slender, long green pods but susceptible to rust. Inheritance studies indicated that resistance to rust was controlled by a single, dominant gene. Pedigree method of breeding was followed for incorporating rust resistance in to commercially cultivated varieties. Breeding lines with resistance to rust were selected to F2 generation onwards. These were advanced up to F7, wherein, a promising line, (Arka Bold x Arka Komal) 99-17-2-1-4-12-3, with resistance to rust with high pod yield and good pod quality was selected and named Arka Anoop and released for commercial cultivation.